IUE Spectra of Seyvert 1 Galaxy NGC 7469- BLR Characteristics of NGC 7469 - Dong-Hoon Son; Siek Hyung (Journal of Astronomy and Space Sciences, 2005)
From the line ratios of Si III] 1892 to C III] 1909 (Feibelman & Aller 1987), we estimated the BLR electron densities and their changes of Seyfert 1 galaxy NGC 7469 using IUE spectra observed from June 11 to July 29, 1996 (Wanders et al. 1997). We separated blended Si III] and C III] lines using the STARLINK/DIPSO and measured their fluxes within the error of 12.4% and 6.6%, respectively. Electron density fluctuated from 109.69 to 1010.93 during about two month period, i.e. 17.3 times density variation within 50 days. We also derived time delays from UV emission line variations relative to the continuum (at 1315Å): 2 days for C IV, 4 days for C III], 8 days for Si III]. This suggests that their stratified UV line emission regions are at 0.002 pc, 0.004 pc and 0.006 pc, respectively, from the central region. Based on the BLR sizes and their rotation velocities deduced from the line profiles, we estimate the central black hole mass as about 106 M⊙.